The Clinical Efficaciency and the Cost-Effectiveness of Reperfusion Therapy in Myocardial Infarction - A. M. Nazarov; R. I. Saifutdinov (Архивъ внутренней медицины)
The goal of the research was to value the cost-effectiveness and the efficacy of reperfusion therapy in myocardial infarction including one — year prospective examenation.Methods. The immediate and long-term results of reperfusion therapy in myocardial infarction with ST-elevated (MISTE) were analyzed. The immediate results of reperfusion therapy were estimated in 349 patients with MISTE by the hospital mortality, the duration of hospitalization, the length of treatment in the resuscitation and intensive care unit. The long-term results were estimated in 137 MISTE patients by the frequency of emergency call-outs and the frequency of hospital admissions for ischemic heart disease (IHD) within the post-infarction period. The costs of hospital treatment, reperfusion therapy, emergency call-outs and out-patient treatment were calculated using the rates of compulsory medical insurance fund. The lost years of potential life and open amount of Domestic Product due to premature mortality were also calculated.Results. The hospital mortality was 2.9 times less in the patients with MISTE who received reperfusion therapy, than in the patients who did not. Reperfusion therapy was attended with reduction of the duration of hospitalization and the length of treatment in the resuscitation and intensive care unit. Economic benefit as a result of the increase of labor potential due to hospital mortality reducing with reperfusion therapy in MI was higher than financial expenditure of reperfusion therapy. The frequency of hospital admissions for IHD within the post-infarction period per one patient was less in the patients with MI who received reperfusion therapy than in patients who did not. There were not significant differences between two groups of patients — with and without reperfusion therapy — in view of the frequency of emergency call-outs for IHD. There was little percentage of patients treated by the therapist and the cardiologist in out-patient departments in both groups of the patients throughout the year after MI.Conclusion. Reperfusion therapy is effective and profitable in the patients with MISTE. However the low quality of periodic health examination within the post-infarction period probably impairs the long-term results of fibrinolytic therapy and angioplasty and raises the risk of investment to reperfusion therapy in the patients with MI.